2019
DOI: 10.1596/978-1-4648-1499-0
|View full text |Cite
|
Sign up to set email alerts
|

Learning Environments and Learning Achievement in the Russian Federation: How School Infrastructure and Climate Affect Student Success

Abstract: Books in this series are published to communicate the results of Bank research, analysis, and operational experience with the least possible delay. The extent of language editing varies from book to book. This work is a product of the staff of The World Bank with external contributions. The findings, interpretations, and conclusions expressed in this work do not necessarily reflect the views of The World Bank, its Board of Executive Directors, or the governments they represent. The World Bank does not guarante… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…The study by Sawitri et al (2019) and Shirrell et al (2019) shows that physical infrastructure plays a crucial role in influencing student learning achievement. This is supported by other research conducted by Setiawan et al (2018), Shmis et al (2019), and Nafis and Muchtar (2020). However, research that specifically focuses on planning, implementation and evaluation of the management of educational facilities and infrastructure in public high schools is still limited.…”
Section: Introductionmentioning
confidence: 74%
“…The study by Sawitri et al (2019) and Shirrell et al (2019) shows that physical infrastructure plays a crucial role in influencing student learning achievement. This is supported by other research conducted by Setiawan et al (2018), Shmis et al (2019), and Nafis and Muchtar (2020). However, research that specifically focuses on planning, implementation and evaluation of the management of educational facilities and infrastructure in public high schools is still limited.…”
Section: Introductionmentioning
confidence: 74%
“…Infrastructure is essential for creating a suitable environment for teachers to efficiently deliver knowledge to their students (Gray & DiLoreto, 2016;Marquez-Ramos & Mourelle, 2019). At the same time, in achieving students' academic success, one of the most frequently observed hindrances across different regions is a sub-standard level of school infrastructure (Cuesta et al, 2016;Shmis et al, 2019). Studies have found that better infrastructure access improves student success (Marquez-Ramos & Mourelle, 2019;Huebener et al, 2017).…”
Section: Covid Education and The Society: A Backgroundmentioning
confidence: 99%
“…This assessment goes beyond traditional academic achievement and encompasses various aspects, such as the physical setting, teacher-student interactions, and curriculum effectiveness. Several international studies have illustrated the transformative impact of the School-Age Care Environment Rating Scale, hereafter referred to as SACERS, on educational practices (Shmis et al, 2019). Research findings by Kwon and Park (2020) highlighted the fact that the implementation of the scales in diverse countries led to targeted improvements in educational environments and teaching methodologies.…”
Section: Introductionmentioning
confidence: 99%